Time scales of adaptive behavior and motor learning in the presence of stochastic perturbations - Schöllhorn, W. I.; Mayer-Kress, G.; Newell, K. M.; Michelbrink, M. (Human Movement Science, 2009)
In this paper, the major assumptions of influential approaches to the structure of variability in practice conditions are discussed from the perspective of a generalized evolving attractor landscape model of motor learning. The efficacy of the practice condition effects is considered in relation to the theoretical influence of stochastic perturbations in models of gradient descent learning of multiple dimension landscapes. A model for motor learning is presented combining simulated annealing and stochastic resonance phenomena against the background of different time scales for adaptation and learning processes. The practical consequences of the model`s assumptions for the structure of practice conditions are discussed, together with their implications for teaching and coaching.